North Indian winter fog, barbed wire, drunken driving and neck trauma - Munjal, Manish; Munjal, Shubham; Trehan, Munish; Berry, Amit; Biswas, Gautam; Kaur, Hardeep; Sandhu, Lovleen; Arora, Anurima; Bharadwaj, Iti; Mehta, Devambika; Rekhi, Arshdeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Inebriated motor cyclists in dense fog of North Punjab often lose control and run into the barbed village fencing. The wire drapes the front of the neck and penetrates the tissues to varying depth, depending on the intensity of trauma. This is commonly noted between the cricoids and the mandible. Timely surgical intervention, intoxication and speed checks can reduce the incidence of poor visibility related mishaps. An individual sustained and survived penetrating barbed wire injury by wrapping his head gear around his neck and drove to a rural health care facility for a primary repair of his neck.